Hyaluronic acid/poly(amidoamine) dendrimer nanoparticles for central nervous system applications: in vitro and in vivo studies - Silva, Barbara L. (2012)
Central nervous system (CNS) disorders are among the diseases with less efficiency in treatment. In order to reach its target and exert its effect within the brain parenchyma, drugs must overcome the blood brain barrier (BBB) and the blood-cerebrospinal fluid-brain (BCSFB). The aim of this work was to develop a novel nano-based dendrimer which could serve as a nanocarrier with the ability to cross these barri- ers. Hyaluronic acid/poly(amidoamine) dendrimer nanoparticles (HA/ PAMAM NPs) were synthesized and a detailed physicochemical charac- terization was performed. Results from DLS analysis showed that these HA/PAMAM NPs possessed a mean diameter of 61.23 nm. The HA/PA- MAM NPs were negatively charged and had a low polydispersity factor, which indicates a narrow size distribution. Moreover it was also possi- ble to bind them to fluorochromes, such FITC, in order to trace them in biological environments. In vitro biological assays revealed that HA/PA- MAM NPs did not cause any cytotoxic effect on the viability and prolif- eration of neuronal and glial primary cell cultures. It was also possible to observe that the fluorescent-labeled NPs could be in vitro internal- ized by glial, neuronal and endothelial cells. Finally, in vivo assays revealed that these nanoparticles could be found in the brain paren- chyma upon intrathecal injections. Further studies will focus on testing these systems in relevant models of CNS injury and degeneration.